Identifying distinct latent classes of pitch-shift response consistency: Evidence from manipulating the predictability of shift direction - Ning, Li-Hsin (Frontiers in Psychology, 2022)
Auditory feedback plays an important role in regulating our vocal pitch. When pitch shifts suddenly appear in auditory feedback, the majority of the responses are opposing, correcting for the mismatch between perceived pitch and actual pitch. However, research has indicated that following responses to auditory perturbation could be common. This study attempts to explore the ways individual speakers would respond to pitch perturbation (using an opposing response or a following response) from trial to trial. Thirty-six native speakers of Mandarin produced the vowel /a/ while receiving perturbed pitch at a random time (500 700 ms) after vocal onset for a duration of 200 ms. Three blocks of 30 trials that differed in the pitch-shift stimulus direction were recorded in a randomized order: (a) the down-only condition where pitch was shifted downwards 250 cents; (b) the up-only condition where pitch was shifted upwards 250 cents; and (c) the random condition where downshifts and upshifts occurred randomly and were equally likely. The participants were instructed to ignore the pitch shifts. Results from the latent class analysis show that at the individual level across trials, 57% of participants were switchers, 28% were opposers, and 15% were followers. Our results support that speakers produce a mix of opposing and following responses when they respond to perturbed pitch. Specifically, the proportion of followers was conditional on the expectancy of pitch-shift stimulus direction: More followers were observed when the pitch-shift stimulus direction was predictable. Closer inspection of the levels of response consistency in different time phases shows that a particular mechanism (opposing or following) was initially implemented; the two mechanisms may alternate in the middle phase; and then finally, the pitch-shift response was featured as a particular mechanism near the end phase.